Aqueous Extract of Rosmarinus officinalis L. Inhibits Neutrophil Influx and Cytokine Secretion. (15th October 2014) - Silva, Ana Mara de Oliveira e; Machado, Isabel Daufenback; Santin, José Roberto; de Melo, Illana Louise Pereira; Pedrosa, Gabriela Vieira; Genovese, Maria Ines; Farsky, Sandra Helena Poliselli; Mancini‐Filho, Jorge
<x xml:space="preserve">Abstract</x> Rosmarinus officinalis L. phenolic compounds have attracted considerable attention because of their antioxidant and antimicrobial properties, including its ability to treat inflammatory disorders. In this work, we investigated the in vivo and in vitro effects of R. officinalis aqueous extract on neutrophil trafficking from the blood into an inflamed tissue, on cell‐derived secretion of chemical mediators, and on oxidative stress. Anti‐inflammatory activity was investigated using carrageenan‐induced inflammation in the subcutaneous tissue of male Wistar rats orally treated with the R. officinalis extract (100, 200, or 400 mg/kg). The leukocyte influx (optical microscopy), secretion of chemical mediators (prostaglandin E2 (PGE2), TNF‐α, interleukin 6 (IL‐6), leukotriene B4 (LTB4), and cytokine‐induced neutrophil chemoattractant 1 by enzyme‐linked immunosorbent assay), and the anti‐oxidative profile (super oxide dismutase (SOD), glutathione peroxidase, and thiobarbituric acid reactive substance (TBARS) spectrophotometry) were quantified in the inflamed exudate. N‐Formyl‐methionine‐leucine‐phenylalanine‐induced chemotaxis, lipopolysaccharide‐induced NO2− production (Greiss reaction), and adhesion molecule expression (flow cytometry) were in vitro quantified using oyster glycogen recruited peritoneal neutrophils previous treated with the extract (1, 10, or 100 µg/mL). Animals orally treated with phosphate‐buffered saline and neutrophils incubated with Hank's balanced salt solution were used as control. R. officinalis extract oral treatment caused a dose‐dependent reduction in the neutrophil migration as well as decreased SOD, TBARS, LTB4, PGE2, IL‐6, and TNF‐α levels in the inflamed exudate. In vitro treatment with R. officinalis decreased neutrophil chemotaxis, NO2− production, and shedding of L‐selectin and β2 integrin expressions. Results here presented show that R. officinalis aqueous extract displays important in vivo and in vitro anti‐inflammatory actions by blocking pathways of neutrophil migration and secretion, suggesting its therapeutic application to acute inflammatory reactions. Copyright © 2014 John Wiley & Sons, Ltd.